Effect of sowing and micronutrients foliar spray on lentil (Lens culinaris) in West Bengal - KUMARI, V VISHA; NATH, RAJIB; SENGUPTA, KAJAL; BANERJEE, SAON; DUTTA, DEBJANI; KARMAKAR, SNEHASHIS (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted consecutively during 2018-19 and 2019-20 cropping seasons at Bidhan Chandra Krishi Viswavidyalaya, Mohanpur. The study was carried out in split-plot design having two sowing dates (November first week and December first week) in main plot, and foliar spray (no spray, spray of tap water, Zn @ 0.5% (ZnSO4.7H2O), Fe @ 0.5% (FeSO4.7H2O), B @ 0.2% (Borax 10.5%), Zn @ 0.5% + B @ 0.2%, Zn @ 0.5% + Fe @ 0.5%, B @ 0.2% + Fe @ 0.5% and Zn @ 0.5% + Fe @ 0.5% + B @ 0.2%) in sub-plots with three replications. Pooled results of two years experiment clearly indicated that November sown crop produced significantly (P>0.05) higher growth attributes, yield attributes and yield. November sown crop recorded 52.9%, 58.3%, 11.3% and 3.0% higher number of pods, seed yield, stover yield and test weight compared to the crop sown in December. Foliar spraying of micronutrients, viz. B @ 0.2% + Fe @ 0.5% produced significantly higher seed and stover yield of 1438 kg/ha and 3981 kg/ha respectively, which were 58.3% and 27.0% more than that obtained from the control treatment (772 and 3134 kg/ha). Delay in sowing of crop from November to December reduced the crop duration by 11.4 days (113.4 days vs 101.7 days) which affected the yield of the crop. Overall, it can be concluded that lentil sown during November along with foliar spray B @ 0.2% + Fe @ 0.5% can improve the yield in new alluvial zone of West Bengal, India.